A Portable Non-Invasive Blood Glucose Monitoring Device with IoT - Anis, Siti Nur Shahidah; Alias, Rozlan (Evolution in Electrical and Electronic Engineering, 2021)
Diabetes Mellitus is one of the most life-threatening diseases worldwide and can affect anyone regardless of their age. To avoid the high risk of diabetics, it is important to monitor blood glucose levels regularly. Nowadays, there are many types of blood glucose gauges in health centers that help patients with high blood glucose problems monitor their blood glucose levels. However, most blood glucose measuring devices on the market are invasive, involving finger piercings. This method is high in accuracy but is usually painful and has a higher risk of infections. Therefore, to avoid the anxiety of the invasive glucose monitoring system, it is desirable to develop non-invasive blood glucose monitoring at a low cost. Alternatively, non-invasive techniques were introduced to develop painless glucose measurement methods. In this project, a portable non-invasive blood glucose monitoring device was developed using near-infrared sensors. This sensor is placed at the fingertip to optionally measure blood glucose and blood glucose concentrations are calculated depending on the intensity of light received. The signal is then filtered and amplified before being inserted into the microcontroller. The glucose level of the patient was predicted based on the analyzed voltages received and data of glucose to be displayed on the LCD and was sent to a mobile phone via Wi-Fi. It's displayed through an Android application like Blynk Apps. The Experiment of Glucose Concentration Calibration is showed that these two variables have a negatively strong linear relationship, voltage decreases as glucose concentration increases. Lastly, the percentage difference obtained from the reliability test was less than 25%, which proved that the non-invasive technique was implemented in the device is reliable to measure blood glucose concentration.